Patients' Compliance with Tuberculosis Medication in Ghana: Evidence from a Periurban Community. (1st February 2015) - Danso, Evans; Addo, Isaac Yeboah; Ampomah, Irene Gyamfuah
Abstract : Globally, an estimated 2 million deaths occur every year as a result of tuberculosis. Ghana records over 46, 000 new cases annually despite numerous efforts to curb the disease. One major challenge associated with the control of the disease is patients' noncompliance with medication. Despite the noncompliance setback, not much information is available on the issue. This paper, therefore, examines patients' compliance with medication at the Suhum Kraboa Coaltar District in Ghana. A cross-sectional descriptive study was carried out using interview schedules. Data were primarily retrieved from 40 treatment supporters, in addition to 110 previously treated persons registered in 2010 and 2011 with cases of pulmonary tuberculosis. Evidence from the study indicates that 63 percent of the previously treated persons complied with medication which is below the expected national target of at least 85 percent. However, those with treatment supporters significantly complied with medication. Depression, substance abuse, financial problems, and long duration of treatment were other issues that discouraged patients' adherence to medication. Some patients also attributed supernatural explanations to the source of the disease which negatively affected compliance. Conclusively, future approaches aimed at controlling/eradicating tuberculosis in the district should consider counselling, economic empowerment packages, and detailed education for patients.